Length dependence of activation studied in the isovolumic blood-perfused dog heart - Tucci, P. J.F.; Bregagnollo, E. A.; Spadaro, J. (Wolters Kluwer, 1984)
In studies utilizing the isolated isovolumic blood-perfused canine heart, left ventricular pressure was measured following a sudden expansion of ventricular volume. An increase in performance occurred in two phases: first, there was an instantaneous rise of developed pressure simultaneous with ventricular distension; in the second phase, developed pressure continued to increase for several minutes until a final steady state was reached. The immediate increase in developed pressure occurred with a prolongation of the time-to-peak pressure, and there was no further change of time-to-peak pressure during the time-dependent increase of developed pressure. In another series of experiments, systolic pressure was elevated without changing resting volume, and mechanical performance changed in a different manner: after an increase in systolic load, there was a modest and transient decrease of developed pressure; thereafter, ventricular pressure recovered only to original values. The influence of different degrees of ventricular expansion, calcium, and verapamil were studied. Under higher ventricular dilations the immediate as well as the slow increase of contraction were heightened and the time to reach half of the slow increase was shortened. When ventricular dilation was induced during an infusion of calcium chloride, higher values for the immediate pressure increase were observed, whereas the time-dependent increase and the time to reach half of the slow increase did not change in comparison with control studies. Verapamil decreased the immediate and the time-dependent enhancement of contraction. The time-dependent increase in developed pressure occurs more slowly with verapamil. These findings in the intact heart are in accord with the hypothesis that myocardial stretch is followed by an increase in intracellular calcium stores, and with the concept that the Frank-Starling mechanism involves an activation of the contractile state.